Achieving political acceptability for new transport infrastructure in congested urban regions. (June 2016) - Westin, Jonas; Franklin, Joel P.; Proost, Stef; Basck, Pierre; Raux, Charles
Highlights: Analyzing political acceptability of road pricing using model of political process. Low political support for efficient pricing not explained by lack of acceptability. Conflicting interests make non-efficient policies more attractive to policy makers. To get support for efficient road pricing more focus on political process is needed. Abstract: This paper analyzes the efficiency and political acceptability of road pricing and infrastructure policies targeted at relieving urban congestion. It combines a stylized transport model of an urban road network with a model of the political process that incorporates interactions between voters, citizen interest groups and politicians to explore the possibilities to reach political acceptability for efficient transport policies. In a numerical illustration, the paper compares a set of pricing and investment policies in terms of efficiency and acceptability. The illustration shows how conflicting interests can lead to non-efficient policies being chosen.